An association of AKT1 gene polymorphism with antidepressant treatment response. (2nd April 2016) - Losenkov, Innokentiy S.; Vyalova, Natalya M.; Simutkin, German G.; Bokhan, Nikolay A.; Ivanova, Svetlana A.
Abstract: Objectives : Nowadays it is considered that protein kinase Akt1 could be involved in pathogenesis of affective disorders. We have examined whether AKT1 gene polymorphisms are associated with antidepressant treatment response. Methods : The study included 106 Caucasian patients with depressive disorders from Siberia and 103 healthy control donors. The frequencies of single nucleotide polymorphisms rs1130214 and rs3730358 of AKT1 gene were examined. Results : A comparison of genotypic or allelic frequencies between the groups of healthy donors and depressive patients showed no statistically significant difference. No association between the polymorphisms under study and the scores according to Hamilton Depression Rating Scale 17 was found. However, an association between treatment response assessed by the Clinical Global Impression – Improvement scale and rs1130214 polymorphism was observed. Conclusions : AKT1 gene polymorphism rs1130214 is associated with antidepressant treatment response in patients with depressive disorders.